commutative for addition

<span>22+(m+8)=(m+8)+22</span> then associative
<span>(m+8)+22=m+(8+22)</span>
<span>=m+30</span>

**Answer and Explanation:**

Suppose Waheeda needs x more dollars.

Right now, she has $15. She needs x more, so we add x to 15. The end result we hope to have is $75. So, the equation is:

x + 15 = 75

To solve, we simply subtract 15 from both sides: x = 75 - 15 = 60

Thus, she still needs $60.

Hope this helps!

**Answer:**

here is your answer........

**Answer:**

x = 3

**Step-by-step explanation:**

Multiply the first equation by -1, then add it to second equation.

2x+9y = -12

-2x-7y = 8

-------------------

2y = -4

Solve for y

2y = -4

y = -2

Plug value of y into one of the equations and solve for x

2x + 9(-2) = -12

2x = 6

x = 3